Radiological evaluation of fusion patterns after Lateral Lumbar Interbody fusion with 3D-printed porous titanium cages vs. conventional titanium cages - Velluto, Calogero; Mundis, Gregory; Scaramuzzo, Laura; Perna, Andrea; Capece, Giacomo; Cruciani, Andrea; Inverso, Michele; Borruto, Maria Ilaria; Proietti, Luca (Frontiers in Surgery, 2024)
IntroductionThe assessment of segmental fusion after Lateral Lumbar Interbody fusion (LLIF) using 3D-printed porous titanium cage is still not well studied. Various criteria, such as the presence of bone bridges (BB) between adjacent vertebrae, serve as indicators for anterior fusion. However, limited radiological studies have investigated zygapophyseal joints (ZJ) status following LLIF with porous titanium cages vs. conventional titanium threaded cages. The porous design of the latest titanium intervertebral cages is thought to enhance the bone-to-implant fusion rate. This radiological study aimed to compare the fusion patterns post-LLIF using 3D-printed porous titanium cages against those using threaded titanium cages. This radiological study aimed to compare the fusion patterns after LLIF using 3D-printed porous titanium cages against those using threaded titanium cages.Material and methodsThis retrospective, single-center radiological study involved 135 patients who underwent LLIF and posterior percutaneous screw fixation for degenerative spondylolisthesis. The study included 51 patients (Group A) with the novel porous titanium cages and 84 patients (Group B) with conventional threaded titanium cages. Inclusion criteria mandated complete radiological data and a minimum follow-up period of 24 months. The study evaluated intervertebral bone bridges (BB) for anterior fusion and zygapophyseal joints (ZJ) ankylotic degeneration, based on Pathria et al., as evidence of posterior fusion and segmental immobilization.ResultsTwo years after surgery, intervertebral BB were identified in 83 segments (94.31%) in Group A and in 87 segments (88.77%) in Group B. ZJ Pathria grade I was observed in 2 segments (2.27%) of Group A and in 4 segments (4.08%) of Group B. Grade II was seen in 5 segments (5.68%) of Group A and in 6 segments (6.12%) of Group B. Posterior fusion, classified as grade III, was found in 81 segments (92.04%) of Group A and 88 segments (89.79%) of Group B. Subsidence incidence was 5.88% (3 segments) for the novel cage and 9.88% (8 segments) for the conventional cage.ConclusionsThe architecture of porous titanium cages offers a promising solution for increasing bone ingrowth and bridging space, supporting successful spinal fusion while minimizing the risk of subsidence.